2017
DOI: 10.18203/2349-2902.isj20171635
|View full text |Cite
|
Sign up to set email alerts
|

Primary closure versus T-tube drainage after laparoscopic choledocholithotomy: a prospective randomized study

Abstract: Background: Traditionally laparoscopic common bile duct exploration is followed by T-tube placement because of which patients suffer problems related to T-tube thereby increasing the morbidity of patients. Primary closure of CBD following laparoscopic choledocholithotomy is now being considered as an alternative superior to the traditional method. This study is designed to analyse the outcome of primary CBD repair in terms of mean operation time, duration of hospital stay and post-operative morbidity.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…A total of 369 articles were identified through the electronic database search (368 articles) and manual search (one article); the manually retrieved study 21 was identified from the reference list of one of the other relevant articles. 22 After reviewing the titles and abstracts of these obtained articles, 339 were excluded because they were irrelevant studies, noncontrol studies, systematic reviews, animal studies, or studies that focused on open common bile duct exploration (CBDE).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 369 articles were identified through the electronic database search (368 articles) and manual search (one article); the manually retrieved study 21 was identified from the reference list of one of the other relevant articles. 22 After reviewing the titles and abstracts of these obtained articles, 339 were excluded because they were irrelevant studies, noncontrol studies, systematic reviews, animal studies, or studies that focused on open common bile duct exploration (CBDE).…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of the 30 remaining studies were then assessed. Finally, 26 studies 9,12,21,2345 were eligible for this meta-analysis. Seven were randomized controlled trials, 9,21,23,24,38,42,43 and the other 19 were retrospective cohort studies or prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations